The role of responsive feeding in overweight during infancy and toddlerhood: a systematic review - DiSantis, KI (Int J Obes (Lond), 2011)
A chronic mismatch of caregiver responsiveness to infant-feeding cues, such as feeding when the infant is not hungry, is hypothesized to have a role in the development of overweight by impairing an infant’s response to internal states of hunger and satiation. Although this concept of mismatch or discordance has long been acknowledged in scholarly writings, a systematic assessment of the evidence supporting the role of discordant responsiveness during infant feeding in the early origins of overweight is lacking. This review was undertaken to assess evidence for this hypothesized relationship between discordant responsiveness in feeding and overweight in infancy and toddlerhood, framed within the larger social-environmental context of the infant–caregiver dyad. A systematic method was used to extract articles from three databases of the medical, psychology and nursing fields. The quality of evidence collected was assessed using Oxford University Centre for Evidence Based Medicine’s level of evidence and through a narrative review. The systematic search resulted in only nine original research studies, which met a priori inclusion/exclusion criteria. Several studies provide support for the conceptual model, but most were cross-sectional or lower quality prospective studies. The need for consistent definitions, improved measures and longitudinal work is discussed. In conclusion, this review reveals preliminary support for the proposed role of discordant responsiveness in infant/child overweight and at the same time highlights the need for rigorous investigation of responsive feeding interactions in the first years of life.